Quality assurance and improvement of micro-scale meteorological models. (8th February 2011) - Schatzmann, Michael; Britter, Rex
Models have begun to play an important role in environmental assessment and urban climate studies. Their increasing use, however, is paralleled by a growing awareness that the majority of these models have never been the subject of rigorous evaluation. Consequently there is a lack of confidence in the modelled results. The paper reports on a European initiative (COST 732) which was launched 2005 with the purpose of establishing a generally accepted procedure for the improvement and quality assurance of micro-scale meteorological models that are applied for predicting flow and transport processes in urban or industrial environments.